2002
DOI: 10.1007/s00436-002-0689-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the immune response induced by a carbohydrate enriched fraction from Echinococcus granulosus protoscoleces in patients with cystic hydatid disease

Abstract: The serological and cellular immune response against a carbohydrate-enriched fraction of Echinococcus granulosus (E4+) was studied in a group of patients with cystic hydatid disease (CHD). The profile of IgG subclass against E4+ and the native non-enriched extract (protoscolex somatic antigen, PSA) were compared. A relatively higher ratio of IgG2:IgG4 was induced by E4+ than by PSA (12.4 vs 3.6 respectively). Serological data were associated with clinical parameters dealing with the outcome of disease. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…More interestingly, E4+ induces high levels of IL-10 in vitro in naive peritoneal cells (Dematteis et al, 2001). Furthermore, Cardozo et al (2002) demonstrated that E4+ is immunogenic also in humans. The stimulation with E4+ of PBMC cultures from healthy donors as well as from patients with cystic hydatid disease evoked the production of higher levels of IL-10 than with the crude extract.…”
Section: Article In Pressmentioning
confidence: 95%
“…More interestingly, E4+ induces high levels of IL-10 in vitro in naive peritoneal cells (Dematteis et al, 2001). Furthermore, Cardozo et al (2002) demonstrated that E4+ is immunogenic also in humans. The stimulation with E4+ of PBMC cultures from healthy donors as well as from patients with cystic hydatid disease evoked the production of higher levels of IL-10 than with the crude extract.…”
Section: Article In Pressmentioning
confidence: 95%
“…ϩ is defined through immunoreactivity with the monoclonal antibody (MAb) E492/G1, and more-recent studies on the immune response in humans have suggested a possible role for E4 ϩ during the course of infection with E. granulosus (7).…”
mentioning
confidence: 99%
“…In humans, specific immune response against somatic and/or secreted components of PSC has been reported during chronic disease (Sterla et al 1999;Cardozo et al 2002;Virginio et al 2003;Lorenzo et al 2005). AgB represents a major antigenic component secreted by germinal membrane and PSC (Sanchez et al 1991), which is present in large quantities in the hydatid fluid of fertile cysts (Mamuti et al 2006), but the current knowledge on its biological roles is limited.…”
Section: Discussionmentioning
confidence: 99%